Bilinguisme et apprentissage précoce des langues Entre idées reçues et fausses croyances - Comblain, Annick (Essai, 2023)
In 2022, there are nearly 7.7 billion people on the planet, more than half of whom use more than one language every day. While the need to be bilingual is becoming increasingly important in an increasingly globalised world with large migratory movements, there are still many questions among the general public about the impact of learning two languages on young children. This book addresses the main questions that parents and language professionals have about early bilingualism, whether familial or not, and about school bilingualism, whether voluntary or not. How can we learn/teach languages effectively to children? When to start learning languages? What to do with children with a migrant background? Speaking the language of origin at home? Is it a taboo subject? Are there any risks in introducing a foreign language early in a child's life? Can early bilingualism cause delays or even disorders in language development and school learning? These are some of the questions the author tries to answer. The book is divided into ten points of interest and about thirty questions. She also examines a series of preconceived ideas about bilingualism, its advantages and disadvantages, and analyses them in the light of contemporary scientific research. This book is aimed at a wide audience wishing to obtain objective information on the advantages but also the potential disadvantages of a bilingual education. Annick COMBLAIN is a Doctor of Logopaedics (speech therapy) from the University of Liege. In 1989, she entered the field of early bilingualism by being involved in the creation of the first school language immersion programme in French-speaking Belgium. Since then, she has been a member of the scientific support committee of several language immersion schools. She currently teaches the psychology of bilingualism and multilingualism at the University of Liege. Her research focuses on the impact of bilingual education on children with disabilities.